PHYTOTHERAPEUTIC ACTIVITY OF EUPHORBIA CYPARISSIAS EXTRACTS ON IXODIDAE (ACARI) FEMALE TICKS - Cristina, Romeo Teodor; Morariu, Sorin; Cernea, Mihai S.; Dumitrescu, Eugenia; Muselin, Florin; CumpanaÈ™oiu, Ciceronis (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Given its numerous biologically active components, Euphorbiaceae has been found to be a large plant family and polyvalent with quite interesting therapeutic activity that can be studied. Materials and Methods: The ixodicidal activity of Euphorbia cyparissias extracts was studied in vitro and in vivo. Tested concentrations were 10, 5, 2, 1, 0.5 and 0.25%. Results: For the in vitro study, conducted on field-collected female specimens of Dermacentor marginatus and Haemaphysalis punctata, the efficacy results showed that the ticks died after exposure in the case of 10, 5, and 2% tincture concentrations. The effects appeared after 30 minutes and became more visible 120 minutes after each exposure. The statistical differences regarding the used concentrations were found to be: F = 6.51, df = 5, P < 0.001. The in vivo study of the efficacy of E. cyparissias concentrations was performed on 35 naturally infested sheep and on 30 bovines parasitized with Ixodes ricinus, sprayed with tincture and glycerinate dilutions (bovines) on days 0 and 7. The results revealed detrimental effects on the survivability of female ticks, the most prominent being the reduction of their movement capacity. In sheep in vivo efficiency observed within 24 hrs varied, between 1 and 23% for D. marginatus and between 7 and 27% for H. punctata and respectively between 2 and 53% after 24 hrs, for I. ricinus, comparable effects being also found 72 hrs after the second administration of Euphorbia extracts. Conclusion: Extracts from E. cyparissias may be used, with results, as an ecologic alternative tick control management method, being a cheap solution, with a sizeable role in reducing the use of synthetic and/or other harming and resistance source ixodicidal conditionings.